Ternary Solid Dispersions: A Review of the Preparation, Characterization, Mechanism of Drug Release, and Physical Stability - Arif Budiman; Eli Lailasari; Neng Vera Nurani; Ellen Nathania Yunita; Gracia Anastasya; Rizqa Nurul Aulia; Ira Novianty Lestari; Laila Subra; Diah Lia Aulifa (MDPI AG, 2023)
The prevalence of active pharmaceutical ingredients (APIs) with low water solubility has experienced a significant increase in recent years. These APIs present challenges in formulation, particularly for oral dosage forms, despite their considerable therapeutic potential. Therefore, the improvement of solubility has become a major concern for pharmaceutical enterprises to increase the bioavailability of APIs. A promising formulation approach that can effectively improve the dissolution profile and the bioavailability of poorly water-soluble drugs is the utilization of amorphous systems. Numerous formulation methods have been developed to enhance poorly water-soluble drugs through amorphization systems, including co-amorphous formulations, amorphous solid dispersions (ASDs), and the use of mesoporous silica as a carrier. Furthermore, the successful enhancement of certain drugs with poor aqueous solubility through amorphization has led to their incorporation into various commercially available preparations, such as ASDs, where the crystalline structure of APIs is transformed into an amorphous state within a hydrophilic matrix. A novel approach, known as ternary solid dispersions (TSDs), has emerged to address the solubility and bioavailability challenges associated with amorphous drugs. Meanwhile, the introduction of a third component in the ASD and co-amorphous systems has demonstrated the potential to improve performance in terms of solubility, physical stability, and processability. This comprehensive review discusses the preparation and characterization of poorly water-soluble drugs in ternary solid dispersions and their mechanisms of drug release and physical stability.